Interaksi Simbolik Pengikut Gus Dur Dalam Syiar Dan Dakwah Pada Akun Instagram @Jaringangusdurian - Nur Aulia Fazri, M. Iqbal (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
Transformation of Gus Dur's da'wah thoughts for Gus Dur's followers towards social media Instagram @jaringangusdurian using Gus Dur's photo and video content. Because taking care so that there is still the preaching of Gus Dur's thoughts. Thus, the analysis in this study focuses on the symbolic interaction of Gus Dur's followers in preaching and da'wah on Instagram photos and videos @jaringangusdurian in 2021-2022, totaling 43 photos and 41 videos. The theory used is symbolic interaction from George H. Mead about symbols and meanings to explain how there is symbolic interaction of Gus Dur's followers on Instagram @jaringangusdurian. The aim is to develop and enrich Gus Dur's theoretical literacy and thought proselytizing. This theory is divided into three studies, namely mind, self, and society. The methodology used is a qualitative approach, with the presentation of the data in the form of narrative content analysis. While the paradigm used is constructivist. Research findings on categorized photo and video posts on Instagram @jaringusdurian. This categorization has symbols and meanings that the symbolic interactions of Gus Dur's followers @jaringusdurian follow the mindset of Gus Dur's 9 main values including: monotheism, humanity, justice, equality, liberation, brotherhood, simplicity, chivalry, and traditional wisdom. Mind (thoughts) in the category "Caring for Gus Dur's Values and Example" corresponds to the side of equality and monotheism, in the category "Imitating the Nation's Teacher" according to the value of having chivalry and traditional wisdom. Self (selfhood) in the category "No Practical Politics" has a value on the side of justice. Society (society) in the category of "Social Movement" has a value of humanity and brotherhood.